Analysis of Business Development Strategies in Increasing Business Income CCTV CV. Jaya Mumpuni Bandar Lampung - Patmarina, Hepiana; Hafidz Isnan, Abdil (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the business development strategy of CCTV Jaya Mumpuni in Bandar Lampung with a focus on increasing competitive advantage and business income through the intended market. The research method used is a descriptive qualitative study with a SWOT analysis approach, with interview and observation techniques as data sources. The results of this study concluded that the company's position is in quadrant II which supports the diversification strategy. The reason the company is in this quadrant is because although there are many threats, CCTV Jaya Mumpuni still has qualified internal strengths. The contribution of this research is that the strategy recommendation given is to use the company's strengths to carry out a diversification strategy in order to achieve company goals and increase CCTV Jaya Mumpuni's business revenue. From the assessment of internal factors, the main strength lies in employees who help with work operations with a score of 0.60. The weakness is the lack of accuracy in recording incoming orders with a score of 0.36. From the results of the analysis of external factors, the main opportunity is to innovate in CCTV installation by offering more complete features with a score of 0.48. Meanwhile, the biggest threat for this company is the high competition with similar businesses with a score of 0.96.